2017
DOI: 10.1021/acs.langmuir.7b00778
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Anchorlipids for Tethered Bilayer Lipid Membranes

Abstract: Tethered bilayer lipid membranes are versatile solid-supported model membrane systems. Core to these systems is an anchorlipid that covalently links a lipid bilayer to a support. The molecular structure of these lipids can have a significant impact on the properties of the resulting bilayer. Here, the synthesis of anchorlipids containing ester groups in the tethering part is described. The lipids are used to form bilayer membranes, and the resulting structures are compared with membranes formed using conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…Neutron scattering showed that the change in spacer segment composition did not increase the hydration of the sub-membrane space which remained low at around 5 volume-% (Andersson et al, 2017). This suggests that the packing density of the inner leaflet also plays a significant role in determining the hydration of the sub-membrane compartment.…”
Section: Tethered Bilayer Lipid Membranesmentioning
confidence: 94%
See 4 more Smart Citations
“…Neutron scattering showed that the change in spacer segment composition did not increase the hydration of the sub-membrane space which remained low at around 5 volume-% (Andersson et al, 2017). This suggests that the packing density of the inner leaflet also plays a significant role in determining the hydration of the sub-membrane compartment.…”
Section: Tethered Bilayer Lipid Membranesmentioning
confidence: 94%
“…The high packing density of fully tethered lipid would likely limit the amount of water in the sub-membrane space even if the hydrophobic conformation of the spacer segment was not a significant factor. Experiments were conducted using a different anchorlipid chemistry (DPhyAL), in which the ethylene glycol spacer was replaced with an ester-based segment that is unable to adopt the same helical conformation as a PEG-based spacer and is also more polar than an ethylene glycol chain (Andersson et al, 2017).…”
Section: Tethered Bilayer Lipid Membranesmentioning
confidence: 99%
See 3 more Smart Citations